2022
DOI: 10.3390/ijerph19148308
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization in Medicine: Are German Medical Students Well Prepared for the Future?

Abstract: The German healthcare system is facing a major transformation towards digitalized medicine. The aim was to find out the attitude and the degree of preparation of upcoming medical professionals for digital medicine. By means of an online survey, medical students from 38 German faculties were asked about different topics concerning digitalization. Most students (70.0%) indicated that they had not had any university courses on digital topics. Thus, only 22.2% feel prepared for the technical reality of digitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 92 publications
0
8
0
1
Order By: Relevance
“…18 However, a recent study found that the vast majority of surveyed medical students from Germany did not feel well prepared for a career in modern medicine that draws on progressively more complex digital technologies, indicating that they were offered hardly any courses focusing on digital competence. 19 This is despite the fact that 93% of surveyed members of medical faculties in Germany agreed that digitalization was essential for medical education, as another study found. 20…”
Section: Competencies Digitalizationmentioning
confidence: 95%
“…18 However, a recent study found that the vast majority of surveyed medical students from Germany did not feel well prepared for a career in modern medicine that draws on progressively more complex digital technologies, indicating that they were offered hardly any courses focusing on digital competence. 19 This is despite the fact that 93% of surveyed members of medical faculties in Germany agreed that digitalization was essential for medical education, as another study found. 20…”
Section: Competencies Digitalizationmentioning
confidence: 95%
“…Moreover, compared to past research that mostly focus on institutional inertia and pedagogical strategies Although it may seem like ndings from this study may not be generalizable to other developed countries given the relatively small number of medical schools in Singapore, the application of relevant constructs within the CFIR that suit the needs of different settings would enable the results to be applied to a global structure. As studies have shown, developed countries such as the U.S, Australia and Germany are also experiencing similar pace of technological development and digitalization of medicine, as well as gaps in implementing a digitally-oriented curricula (Cutrer et al, 2021;Edirippulige et al, 2018;Sorg et al, 2022).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Adrian et al conducted a survey to investigate the attitudes of German medical students towards AI and other digital health applications [ 20 ]. Heiko et al conducted another survey on German medical students to assess their preparation for digitalized medicine [ 31 ]. The survey included 453 students and found only 22% (100/453) of them were prepared for the digital transformation, which can be associated with another finding of this study: 70% (318/453) of these students had not participated in any university courses on digital health.…”
Section: Related Workmentioning
confidence: 99%